KUALITAS PRODUKSI, MANAJEMEN DAN PERSEPSI MASYARAKAT TERHADAP PRODUK UKM RAMBAK CAKAR SEBAGAI UPAVA PENINGKATAN DAVA SAING INDUSTRI KECIL - Choerudin, Achmad (LPPM UNS, 2014)
Small and Medium Enterprises (SME) have various problems, product quality, marketing and business sustain ability. Based on the background of the IbM program has issues about improving the manufacturing process and production rambak cakar that is not too long in the event of rainy weather making it more productive and effective, improving the quality of SME management and marketing strategies of production and seek opportunities to other product variations. The result is the production of tools for increasing productivity rambak dryer with drying peresentase level 60% compared with manual drying, manufacturing of SME management strategy with the creation of training modules SME management, financial planning, the simple balance of SME and marketing through the internet, so it will be more easily recognized and extensive marketing network. For product variations opportunities through market research with the results of (1) the level of public confidence in the SME products is quite high, (2) the need for improvement in brand and packaging SME with proven products that (a) the quality of SME products is not good, (b) no health insurance and ha/al happens almost all food products from SME, besides it does not yet include any food Ingredients Daily Intake and (c) the design of SME products. SME products have the potential to compete with products from non-SME, (3) need to improve the quality of products from a variety of marketing management, human resources and government support.